Characterization of an N-terminal Nav1.5 channel variant - a potential risk factor for arrhythmias and sudden death? - Stefanie Scheiper-Welling; Paolo Zuccolini; Oliver Rauh; Britt-Maria Beckmann; Christof Geisen; Anna Moroni; Gerhard Thiel; Silke Kauferstein (BMC, 2020)
Abstract Background Alterations in the SCN5A gene encoding the cardiac sodium channel Nav1.5 have been linked to a number of arrhythmia syndromes and diseases including long-QT syndrome (LQTS), Brugada syndrome (BrS) and dilative cardiomyopathy (DCM), which may predispose to fatal arrhythmias and sudden death. We identified the heterozygous variant c.316A > G, p.(Ser106Gly) in a 35-year-old patient with survived cardiac arrest. In the present study, we aimed to investigate the functional impact of the variant to clarify the medical relevance. Methods Mutant as well as wild type GFP tagged Nav1.5 channels were expressed in HEK293 cells. We performed functional characterization experiments using patch-clamp technique. Results Electrophysiological measurements indicated, that the detected missense variant alters Nav1.5 channel functionality leading to a gain-of-function effect. Cells expressing S106G channels show an increase in Nav1.5 current over the entire voltage window. Conclusion The results support the assumption that the detected sequence aberration alters Nav1.5 channel function and may predispose to cardiac arrhythmias and sudden cardiac death.